Ring-shaped architecture of RecR: implications for its role in homologous recombinational DNA repair - Lee, Byung Il (2004)
RecR, together with RecF and RecO, facilitates RecA loading in the RecF pathway of homologous recombinational DNA repair in procaryotes . The human Rad52 protein is a functional counterpart of RecFOR. We present here the crystal structure of RecR from Deinococcus radiodurans (DR RecR). A monomer of DR RecR has a two-domain structure: the N-terminal domain with a helix–hairpin–helix (HhH) motif and the C-terminal domain with a Cys(4) zinc-finger motif, a Toprim domain and a Walker B motif. Four such monomers form a ring-shaped tetramer of 222 symmetry with a central hole of 30−35 Å diameter. In the crystal, two tetramers are concatenated, implying that the RecR tetramer is capable of opening and closing. We also show that DR RecR binds to both dsDNA and ssDNA, and that its HhH motif is essential for DNA binding.